1997
DOI: 10.1080/00908319708908866
|View full text |Cite
|
Sign up to set email alerts
|

Coal Cleaning Performance in an Air Fluidized Bed

Abstract: This inuestigation was concerned with the effects of coal properties and process variables, such as fluidized bed depth, superficialgas uelocity, coal to magnetite feed weight ratio, and processing time, on coal cleaning efficiency in a bubblingfluidized bed d y coal purifier. The coal cleaning erperiments were cam'ed out on various size fmctions of Pennsyluania ' s bituminous coal, Rushton coal. Angular magnetite was used as the host material to enhance segregation. The performance of the coal cleaning proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The effective density for immersed object separation in the GSFBCB is apparently affected by the physical properties of immersed objects, such as their size, , shape, , and density. Objects of large size were reported to possibly gain additional weight due to the deposition of defluidized particles on their upper surface, ,,, causing the effective density of large-size objects to be lower than the fluidized bed density. Objects of smaller size, on the other hand, were found to increase their effective density but decrease the separation effectiveness, due to the increasing disturbance by gas bubbles. , For the immersed objects of different shapes, the separation effectiveness decreases with decreasing sphericity, because objects of lower sphericity have a larger specific area (surface area to volume ratio) subject to more viscous effects. , For the immersed objects of different densities, objects with densities close to the fluidized bed density were observed to be easily suspended or move more randomly, whereas objects with densities more different from the bed density were found to float or sink quickly given the higher separation potential. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective density for immersed object separation in the GSFBCB is apparently affected by the physical properties of immersed objects, such as their size, , shape, , and density. Objects of large size were reported to possibly gain additional weight due to the deposition of defluidized particles on their upper surface, ,,, causing the effective density of large-size objects to be lower than the fluidized bed density. Objects of smaller size, on the other hand, were found to increase their effective density but decrease the separation effectiveness, due to the increasing disturbance by gas bubbles. , For the immersed objects of different shapes, the separation effectiveness decreases with decreasing sphericity, because objects of lower sphericity have a larger specific area (surface area to volume ratio) subject to more viscous effects. , For the immersed objects of different densities, objects with densities close to the fluidized bed density were observed to be easily suspended or move more randomly, whereas objects with densities more different from the bed density were found to float or sink quickly given the higher separation potential. …”
Section: Introductionmentioning
confidence: 99%
“…Objects of smaller size, on the other hand, were found to increase their effective density but decrease the separation effectiveness, due to the increasing disturbance by gas bubbles. 37,40 For the immersed objects of different shapes, the separation effectiveness decreases with decreasing sphericity, because objects of lower sphericity have a larger specific area (surface area to volume ratio) subject to more viscous effects. 9, 35 For the immersed objects of different densities, objects with densities close to the fluidized bed density were observed to be easily suspended or move more randomly, whereas objects with densities more different from the bed density were found to float or sink quickly given the higher separation potential.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, fine media particles are transformed from a fixed state to a pseudo-fluid state by fluidizing air through an air distributor plate located at the bottom of vessel. During fluidization as air velocity is increases, the particle bed goes from a fixed bed to a fluidized bed and to a transported bed, respectively [11][12][13][14][15][16]. Zhenfu et al [17] reported that by using the ADMFB a good separation performance was achieved for the 50 Â 6 mm size fraction obtaining clean coal and tailings containing 11.80% and 85.75% ash, respectively, with a Probable Error (Ep) value of 0.03.…”
Section: Introductionmentioning
confidence: 99%